Peran budaya madrasah dalam penanaman sikap moderasi beragam di MAN 1 Kota Probolinggo - Syihabuddin, Moh Hisyam (Maliki Interdisciplinary Journal, 2024)
The aim of this research was to describe the culture carried out in an effort to instill an attitude of religious moderation in MAN 1 Probolinggo City. Obtaining this data includes two aspects, the first aspect is from primary data and the second aspect is from secondary data. The data collection method uses three techniques in the form of observation, interviews and documentation. The results of this research show that in an effort to introduce culture and instill understanding regarding religious moderation, teachers must instill habits from an early age in students. Because students are the next generation of the Indonesian nation who are the support and hope for their parents in the future. Briefly and clearly, the results of the research can be used as input, especially for the government, educational institutions and other stakeholders in determining appropriate policies and programs to promote religious moderation in the school environment. The strategies used to instill an attitude of religious moderation are: First, get used to reciting the Koran in the morning before starting lessons. Second, by getting used to the cult before the congregational midday prayer. Third, by reading Istighasah and Surah Yasin on Friday.